A cautionary tale on the use of antiplatelet treatment following TURP. (4th April 2014) - Murray, Aileen Marie; Keville, Norah; Gray, Sam
Abstract : A pleasant 74-year-old man was discharged home following a complication-free transurethral resection of his prostate (TURP) and successful trial without catheter. Unfortunately, on postoperative day 6, he presented to A&E with chest pain requiring emergency intervention for a confirmed myocardial infarction. A drug-eluting stent was inserted into his right coronary artery and he was started on dual antiplatelet therapy of aspirin and clopidogrel. On day 7, the patient developed significant haematuria requiring transfusion and an obstructive uropathy, requiring an emergency laparotomy and 1 L of organised clot evacuation from his bladder. The dual antiplatelet treatment was restarted on day 4 postlaparotomy, following debate between both the cardiology and urology teams regarding its appropriate reintroduction. On day 7, he was rushed back to the theatre for a re-laparotomy after CT confirmed reaccumulation of clot following an acute deterioration at ward level. The patient made an excellent recovery and was discharged home with regular outpatient follow-up.